2022
DOI: 10.1111/ejh.13779
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the HScore and the HLH‐2004 diagnostic criteria for the diagnosis of hemophagocytic lymphohistiocytosis in a multicenter cohort

Abstract: Timely diagnosis of hemophagocytic lymphohistiocytosis (HLH) is critical and relies on clinical judgment. The HLH‐2004 criteria are commonly used diagnostic criteria, whereas HScore was recently developed for reactive HLH. Objective In this external validation study, we sought to compare the diagnostic accuracy of the HLH‐2004 criteria and HScore and identify optimal cutoffs stratified by underlying etiology. Methods In this retrospective cohort of all hospitalized adults in Alberta, Canada, (1999–2019) who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The two main available scores for HLH diagnosis are currently the HLH-2004 criteria and the Hscore [ 6 , 15 ]. External validation studies revealed that those scores had high sensitivity and specificity, which could vary depending on the scored population [ 7 , 17 ]. HLH-2004 criteria and Hscore perform better in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The two main available scores for HLH diagnosis are currently the HLH-2004 criteria and the Hscore [ 6 , 15 ]. External validation studies revealed that those scores had high sensitivity and specificity, which could vary depending on the scored population [ 7 , 17 ]. HLH-2004 criteria and Hscore perform better in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…HLH-2004 criteria and Hscore perform better in critically ill patients. Hscore performs better in non-IMID-related HLH patients since the original study included only 3% of patients with IMID-related HLH and thus, this linear model is probably unsuitable for populations with a high proportion of IMID-related HLH [ 7 , 16 ]. These performances are to be modulated depending on the cutoff score that is chosen to define HLH when using Hscore.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations